Multiscale test of CAPM for three Central and Eastern European stock markets - Dajčman, Silvo; Festić, Mejra; Kavkler, Alenka (Journal of Business Economics and Management, 2013)
This paper examines the systematic risk and validity of the basic capital asset pricing model of Sharpe (1964), Lintner (1965) and Mossin (1966) in three Central and Eastern European stock markets (i.e. Slovenia, Hungary and Czech Republic). The CAPM is tested on a multiscale basis, building on the Fama and MacBeth (1973) methodology and applying two modern econometric techniques – wavelet analysis and generalized method of moments estimation. Empirical results indicate that the systematic risk and validity of CAPM implications are multiscale phenomena. Empirical evidence in support of CAPM implications in the investigated Central and Eastern European stock markets is found to be weak. The most commonly violated CAPM hypotheses are the zero Jensen's alpha condition, positive market premium, and the non-systematic influence of non-observable variables on the excess returns of stocks in these stock markets.